« C'était bien à l'époque mais l'avenir iko sombre » : Negotiating Nostalgia with and among Ex-Mineworkers in Lubumbashi (DRC) - Waldburger, Daniela, (Africa Multiple ;, 2025)
Why do former mineworkers in Lubumbashi (DRC) remember exploitative working conditions and measures to control their private lives with nostalgia? Building on their 'objects of loss', this book answers this question, foregrounding the voice of so-called 'Départs Volontaires'. The study combines linguistics, anthropology, and archives research to explore what ex-mineworkers regard as material and emotional 'objects of loss'. The book advocates for a participatory research framework called 'the baraza web' which merges the researcher's perspective with the standpoint of the ex-miners to create an alternative archive and to show that power relations within a research setting need constant questioning.